Post-release survival of loggerhead sea turtles (Caretta caretta) incidentally hooked in a North Atlantic pelagic longline fishery - James, Michael C.; Hall, Kelly E.; Bond, Emily P.; Sherrill-Mix, Scott; Plot, Virginie (Frontiers in Marine Science, 2024)
Estimating mortality of sea turtles incidentally captured in fishing gear is essential to understanding fishery impacts on sea turtle populations. Loggerhead turtles (Caretta caretta) are a component of bycatch in pelagic longline fisheries, including those operating in Atlantic Canada. In this study, we used pop-up satellite archival tags (PSATs) attached to 62 loggerhead turtles incidentally hooked in Atlantic Canadian shallow-set pelagic longline gear (2012–2018) to estimate associated post-release survival. Consistent with conventional fishing practices, hooks were not removed from turtles prior to release. Analysis of diving behaviour, ocean temperature, and ambient light level was used to assign fates to turtles. Post-release survival was calculated using the Kaplan-Meier estimator with right censoring. Based on this method, the annual survival probability of an individual loggerhead post-release is 0.877 ± SE 0.052. While it is commonly assumed that hook location is an important variable in predicting fates of turtles after release, there was no difference in survival of deep-hooked (swallowed hook) versus shallow-hooked turtles. These results indicate higher survivorship among hooked loggerheads captured in shallow-set pelagic longline gear than prevailing wisdom and suggest that at least some of the population impacts on loggerhead turtles conventionally attributed to pelagic longline interactions may be linked to other threats.